Student Perceptions of Online Radiologic Science Courses. - Papillion, Erika; Aaron, Laura (Radiologic Technology)
Purpose To evaluate student perceptions of the effectiveness of online radiologic science courses by examining various learning activities and course characteristics experienced in the online learning environment. Methods A researcher-designed electronic survey was used to obtain results from students enrolled in the clinical portion of a radiologic science program that offers online courses. The survey consisted of elements associated with demographics, experience, and perceptions related to online radiologic science courses. Surveys were sent to 35 program directors of Joint Review Committee on Education in Radiologic Technology-accredited associate and bachelor's degree programs with requests to share the survey with students. Results The 38 students who participated in the survey identified 4 course characteristics most important for effective online radiologic science courses: a well-organized course, timely instructor feedback, a variety of learning activities, and informative documents, such as course syllabus, calendar, and rubrics. Discussion Learner satisfaction is a successful indicator of engagement in online courses. Descriptive statistical analysis indicated that elements related to the instructor's role is one of the most important components of effectiveness in online radiologic science courses. This role includes providing an organized course with informative documents, a variety of learning activities, and timely feedback and communication. Conclusion Although online courses should provide many meaningful learning activities that appeal to a wide range of learning styles, the nature of the course affects the types of learning activities used and therefore could decrease the ability to vary learning activities.